The Electability of Islamic Educational Institutions - Bahar Agus Setiawan; Hairul Huda; Sofyan Rofi (Jurnal Pendidikan Islam, 2020)
Islamic schools have participated in Indonesian educational market and they have shown significant developments both in their achievement and their images. Their competitiveness is reflected in the level of their electability which can be investigated from the survey. This study was aimed at investigating the principal component that influenced the electability of Islamic schools with the formulation of any variable problems that contributed significantly to the electability of Islamic schools. This research applied Principal Component Analysis (PCA) with a questionnaire instrument using nine variables with 72 measuring statements. There were 204 respondents took a part from MTsN (Madrasah Tsanawiyyah Negeri/State Islamic Junior High School) 5 Jember and SMPIT (Sekolah Menengah Pertama Islam Terpadu/Integrated Islamic Junior High School) Al-Ghazali Jember. The results of this study showed the principal component in each Islamic school amounted to one with an eigen value of 6.3081 and 6.1140. Based on the result of this study, some variables contributed significantly to the school electability and this was done by continuing the analysis until the proportion value was greater than 80 percent. The variables of principal, teachers and learning atmosphere influenced school electability at MTs Negeri 5 Jember and variables of school principals, teachers and infrastructure influenced significantly school electability at SMPIT Al-Ghazali.